Contratações públicas populares - Costa, Thalles Gomes Camêllo da (2021)
This work aims to build an overview of popular participation in public contracts, having as its scope those carried out in the context of public education, from an analysis that combines sociological and legal dogmatic aspects. Therefore, it seeks to produce, at first, a reflection on the dialectics of sovereignty and the effectiveness of popular participation instruments in the sugarcane region of Alagoas, Brazil, from a dialogue between the legal-administrative doctrine with the perspectives of critical legal studies and insurgent jurisprudence. Then, it promotes an analysis of the tensions between popular public education and the kidnapping of participation mechanisms evidenced by the distortion of the legal regime of partnerships between the public administration and civil society organizations promoted by the bet of the moneyed third moneyed sector and large companies mainly linked to the area of technology in the gradual collapse of the boundaries between State and market. Finally, it outlines legal concepts and possibilities for the consolidation and strengthening of popular public contracts, based on a theoretical pact on what is understood by popular public contracts, nuanced by the critical analysis of concrete cases related to the educational reality